2011
DOI: 10.1038/leu.2011.281
|View full text |Cite
|
Sign up to set email alerts
|

Extreme telomere erosion in ATM-mutated and 11q-deleted CLL patients is independent of disease stage

Abstract: with chromosomal abnormalities, and about half of them carry FLT3-ITD. Chronic phase CML is NPM1 wt , whereas only one case of NPM1 mut myeloid blast crisis CML has been reported. 10 IDH1 and IDH2 mutations are also not found in chronic phase CML but can be found at low frequency in blast crisis CML. 11 Here, we present a CML patient who developed clonal hematopoietic disease (AML) in PhÀ cells, with normal karyotype and NPM1 mut , while being in complete CML molecular remission and without previous MDS phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 8 publications
(21 reference statements)
6
21
0
1
Order By: Relevance
“…Consistent with this view, BrittCompton et al (2011) showed that in comparison to patients who have wild type ATM gene, TLs were significantly shorter in CLL patients with ATM mutations including those with stage A disease. This TL shortening was present in both patients with ATM mutations and 11q deletions and was independent of IGHV gene mutation status, CD38 status and ZAP70 status (Britt-Compton et al, 2011). This provides evidence that defective double-strand break checkpoints, which are known to exist in ATM mutated cells, may lead to extended replication and extreme telomere shortening.…”
Section: Chronic Lymphocytic Leukaemiamentioning
confidence: 61%
“…Consistent with this view, BrittCompton et al (2011) showed that in comparison to patients who have wild type ATM gene, TLs were significantly shorter in CLL patients with ATM mutations including those with stage A disease. This TL shortening was present in both patients with ATM mutations and 11q deletions and was independent of IGHV gene mutation status, CD38 status and ZAP70 status (Britt-Compton et al, 2011). This provides evidence that defective double-strand break checkpoints, which are known to exist in ATM mutated cells, may lead to extended replication and extreme telomere shortening.…”
Section: Chronic Lymphocytic Leukaemiamentioning
confidence: 61%
“…2,3 Subsequent studies have documented associations with unmutated IGHV genes, del13q, genomic complexity, short telomeres, progressive disease and a poor outcome in response to alkylating agent or purine analog treatment, which was improved by their use in combination and ameliorated by the further addition of rituximab. [4][5][6][7][8][9][10] Genomic profiling studies have refined previous karyotypic and FISH studies showing that 11q deletions are mono-allelic, frequently large and include a minimally deleted region (MDR), which encompasses the ATM gene. [11][12][13][14] Evidence that ATM is a key target of 11q deletions is derived from findings that: 1) mutation of the ATM gene is found in 30-40% of patients with an 11q deletion; 15,16 2) the presence of an ATM mutation results in impaired DNA damage responses; 15,[17][18][19] and 3) patients in the UK LRF CLL4 trial with biallelic ATM abnormalities (deletion and mutation) have a poorer outcome following the initial therapy with alkylating agent and/or purine analog therapy compared to those with mono-allelic ATM deletion or mutation.…”
Section: Introductionmentioning
confidence: 99%
“…This study further reinforces the recent suggestion that CLL development is driven by antigenic selection linked with preferential acquisition of specific genetic defects during disease evolution. Stavroula Ntoufa, 4 Zadie Davis, 5 Gunnar Juliusson, 6 Karin E. Smedby, 7 Chrysoula Belessi, 8 Panagiotis Panagiotidis, 9 Tasoula Touloumenidou, 4,10 Frederic Davi, 11 Anton W. Langerak, 12 Paolo Ghia, 13 Jonathan C. Strefford,14 David Oscier, 5 Jiri Mayer, 1 Kostas Stamatopoulos, 4 Sarka Pospisilova, 1,2 Richard Rosenquist, 3 and Martin Trbusek…”
Section: P=0039mentioning
confidence: 99%
“…The prognostic relevance of TL in CLL has been repeatedly reported 9,10 and CLL cells with ATM mutations were recently shown to display extreme telomere shortening, allowing telomere fusions and subsequent large-scale genomic rearrangements facilitating disease progression through increased A B genomic instability. 11,12 Relative telomere length (RTL) was investigated by real-time quantitative PCR as originally described by Cawthon et al 13 with certain modifications (Online Supplementary Appendix). The median RTL value 0.4 (range 0.05-2.25) was subsequently used to distinguish between 'short' and 'long' telomeres.…”
Section: 67mentioning
confidence: 99%